Streptococcus gordonii FSS2 Challisin affects fibrin clot formation by digestion of the αC region and cleavage of the N-terminal region of the Bβ chains of fibrinogen - Harty, Derek W. S.; Farahani, Ramin M.; Simonian, Mary R.; Hunter, Luke; Hunter, Neil (Thrombosis and Haemostasis, 2012)
Bacteria within endocarditis vegetations are encased in fibrin matrix that is resistant to resolution. We have previously shown that FSS2 Challisin, a serine protease from Streptococcus gordonii, is able to hydrolyse the Aα and Bβ chains of fibrinogen and has potent angiotensin converting enzyme (ACE) activity. The alteration in the structure of fibrin formed from FSS2 Challisin-degraded fibrinogen may therefore contribute to the resistant fibrin matrix. To this end, we have investigated the specific interactions of FSS2 Challisin with fibrinogen. FSS2 Challisin extensively degrades the αC region of fibrinogen Aα chains, hydrolysing both the αC-domain and αC-connnector. Additionally, the N-terminal region of the Bβ chains is cleaved twice, at Leu19 and Ser28, removing the B fibrinopeptides and ‘B’ knobs. Substrate analysis indicates FSS2 Challisin has specific requirement for proline two residues before the cleavage point and a neutral or basic un-branched amino acid preceding the cleavage point. Fibrin formation by thrombin was modified and the initiation of fibrinolysis extended, in FSS2 Challisin-treated plasma clots. Digestion of fibrinogen by FSS2 Challisin prior to thrombin action increased fiber density and fiber branch point density. The velocity of fibrinolysis was significantly slower for fibrin formed from FSS2 Challisin-treated fibrinogen but was faster when data was normalised for the increased fibrin density. Thromboelastography of whole blood treated with FSS2 Challisin indicated reduced clot coagulation time and increased shear resistance. Combined ACE and fibrinogenase activities of FSS2 Challisin suggest a pro-coagulant effect of this virulence factor which is conserved in the viridans streptococci.
Keywords: Fibrinogen; fibrin; thrombus; Streptococcus gordonii; infective endocarditis